A study of the limitations of musical experience in Ancient Chinese Poetry – The case of the creation concert of Wei’s Music Score - Zushun Zhang; Panjie Xie; Jinsong Wang (PLoS ONE, 2026)
Ancient poetry, with profound artistic and literary value, holds a prominent position among China’s vocal works. Against the backdrop of vigorously promoting China’s outstanding traditional culture in the new era, it has witnessed a revival in interpretations both domestically and internationally. At present, ancient poetry faces dissemination challenges including constraints in performance environments and limitations in historical comprehension. These experiential restrictions impede recipients’ cultural identity, cultural confidence and cultural inheritance. This study adopts a literature review methodology, integrating the conceptual framework of leisure constraints and tourism research. It conducts systematic research on ancient poetry concerts to develop a scale measuring the limiting factors of ancient poetry experience. Using this scale, the study investigates and analyzes statistical results from three Weishi Yuepu (Wei Dynasty Music Score) creative concerts through the PLS-SEM method. Results indicate that constraints on ancient poetry experience exhibit a three-factor structure comprising personal constraints, interpersonal constraints, and structural constraints. This confirms the sequential pathway of ancient poetry experience: Preference→Participation; Personal Constraint→Preference; Structural Constraints→Participation. The study extends the application of the leisure restrictions model to traditional music, benefiting the domestic and international dissemination of China’s outstanding traditional culture while enhancing recipients’ understanding and interest in ancient poetry.